Conflict, survival and every day resistance in the post-war period: Cinco Villas (Zaragoza) - López Acón, Óscar (Huarte de San Juan. Geografía e Historia, 2023)
In this article we take the geographical space of the Cinco Villas region (Zaragoza) to address the relationship between the consequences of the war, the forms of sociability and the attitudes that regular people put in place in order to survive. To do this, we focus on several aspects such as social unrest over living conditions, the guerrilla phenomenon, property crime, crimes in the hills, poaching, everyday violence and the post-war female experience.